A merciful promise - Elliot, Kendra (Elliot, Kendra. Mercy Kilpatrick novels., 2019)
"The job: infiltrate a militia amassing illegal firearms in an isolated forest community. FBI agent Mercy Kilpatrick is the ideal candidate. She knows Oregon. She's near the compound. And having been raised among survivalists, Mercy understands the mind-set of fanatics. She's ready to blend in. As Mercy disappears into the winter hills, something just as foreboding emerges. Mercy's fiance, Eagle's Nest police chief Truman Daly, is faced with a puzzling series of murders. Now, for Mercy, trapped in a culture where suspicion is second nature, and betrayal is punishable to the extreme, there is no way out. No way to call for help. And as plans for a catastrophic terrorist event escalate, there may be no way to stop them."--Publisher.